VALUE CRISIS OF WESTERN LIBERALISM - Timchishin, B. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2018)
The liberal discourse status in the countries of the West is considered. The vector of liberalism development after Cold War, the increasing of left-wing powers influence on liberalism, their fusion are researched. It is investigated the values analysis of liberal identity from positions of its classics with purpose to find changes and assess them. The examples of negative tendencies, which reveal the accumulated contradictions caused by the absence of external ideological competition are given.